Effectiveness of community-based health promotion in preventing hypertension: A qualitative approach - Eka Mayasari; Serli; Dian Meiliani Yulis; Hairuddin K (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Hypertension remains one of the most prevalent public health issues globally, demanding not only curative but also preventive and promotive strategies. Community-based health promotion programs have emerged as a vital approach to increasing awareness, literacy, and behavioral change to prevent hypertension. Methods: This study employed a qualitative method through a systematic literature review of national and international publications from 2020 to 2025. The selected sources were analyzed thematically to identify social dynamics, intervention models, and determinants of program success. Data analysis involved reduction, display, and interpretation to construct a conceptual model explaining how community-based promotion enhances prevention literacy. Results: The findings indicate that the effectiveness of community-based programs depends on active participation, leadership, resource availability, and integration with primary health services. Empowerment-based education improved knowledge, modified risky behavior, and strengthened cooperation between communities and health workers. The use of digital technologies, such as mobile health applications and social media, expands educational outreach and engagement. Conclusion: Community-based health promotion is a transformative strategy for building awareness, empowerment, and self-reliance in hypertension prevention. Cross-sector collaboration and technology-driven innovation are essential to achieving sustainable outcomes. It is recommended that policymakers and health practitioners strengthen digital literacy, allocate continuous funding, and institutionalize participatory community programs to ensure long-term impact.